Void Space Control in Porous Carbon for High-Density Supercapacitive Charge Storage - Vijayan, Bincy Lathakumari; Nurul Khairiyyah, Mohd Zain; Izan Izwan, Misnon; Reddy, M. Venkatashamy; Adams, Stefan; Yang, Chun-Chen; Anilkumar, Gopinathan M.; Rajan, Jose (American Chemical Society (ACS Publications), 2020)
High density charge (energy) storage under supercapacitive mode requires an electrode which would deliver larger space for charge accumulation and offer larger electrochemical potential difference at an electrode–electrolyte interface. Porous carbon has been a preferred electrode for commercial supercapacitors; however, the charge storability is much lower to the state-of-the-art charge storage devices such as lithium ion batteries. We show that one of the primary limiting factors is the voids in porous carbon, which do not contribute to the capacitance as their sizes are much larger than the size of the solvated/unsolvated ions in the electrolyte. We activate these voids by filling them with a flower-shaped 3D hierarchical pseudocapacitive material (MnCo2O4) by assuming that flower-shaped fillers would provide additional easily accessible surface for charge adsorption. Less than 10wt.% MnCo2O4 in these voids through a simple wet impregnation results in five-fold increase in charge storability of porous carbon from palm kernel shells. Laboratory prototypes of electrochemical double layer capacitors are fabricated using the void-filled-carbon electrodes, which show five-fold higher specific energy than that of pure carbon and are cycled over 5000 times with >95% capacitance retention. The present strategy of activating the voids by hierarchical 3D nanostructures could be applied to build high performance energy storage devices.